Experimental investigation on use of alternative innovative materials for sustainable cooling applications. Issue 5 (3rd September 2021) - Suranjan Salins, Sampath; Reddy, S.V. Kota; Kumar, Shiva
ABSTRACT: In hot regions, the main reason for the consumption of energy arises from cooling the buildings. The intensity of the sunlight also has a direct relation to the use of the cooling systems. In the present work, a humidification system is built with packing made of locally available novel materials, and the performance of the cooling pads has been accessed under both counter flow and cross flow conditions. Coconut coir and wood shaving are used as alternative materials for evaporative cooling, and the experiments are conducted using varied airflow rates and the performance parameters, such as heat flow rate, humidification efficiency, moisture flow rate, coefficient of performance (COP) and specific cooling capacity (SCC) have been tested and compared with the Celdek packing. Results indicated that wood shaving performed better than the coconut coir. Values of COP and SCC are found to be very close to Celdek packing. Humidification efficiency of wood shaving is at par with the Celdek packing with improved quality of indoor air. In addition, results indicated that the counter flow arrangement gave better results compared to cross flow.